Magnetoresistance of Modified Carbon Nanotubes - T.A. Len; I.V. Ovsiienko; L.Yu. Matzui; I.B. Berkutov; I.G. Mirzoiev; D. Gnida; Yu.A. Kunitskyi (Журнал нано- та електронної фізики)
The effect of modification of carbon nanotubes with iron oxides on their electrical and magnetotransport properties is investigated. It was shown that the two-dimensional effects of weak localization and interaction of charge carriers are manifested in electrical and magnetoresistance of modified carbon nanotubes. The temperature dependence of wave function relaxation phase and displacement of the Fermi level in valence band are estimated on the base of low-temperature magnetoresistance date.